Infinite time ruin probability in inhomogeneous claims case - Bieliauskienė, Eugenija; Šiaulys, Jonas (Lietuvos matematikos rinkinys, 2010)
The article deals with the classical discrete-time risk model with non-identically distributed claims. The recursive formula of infinite time ruin probability is obtained, which enables to evaluate the probability to ruin with desired accuracy.
Keywords: discrete time risk model; infinite time ruin probability; inhomogeneous claims